The Loud Unspoken Narratives from Confederate Monuments: How and Why We Should Quiet Them in the Public Square - Green, Shelby D. (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2021)
Traditionally, historic preservation has aimed to protect “collective memory,”—references to a past accepted as commonly shared and collectively commemorated. Collective memory has been used to construct narratives that define communities and urge specific rules and values. In recent years, we have come to see that “collective memory” is indeed “curated memory,” and that memorializing it in public spaces, parks and squares has enabled the assertion of power by the curators over others and has often excluded those others from the stories of the nation. The thousands of statues and namings in honor of the leaders of the Confederacy make this point. If a city’s greatness is found in the quality of its public spaces, the stature and bearing of Confederate memorials there must cause us to rethink our preservation philosophies, as continuing to honor such repugnant figures denies the humanity and worth of those who are targets of the unspoken, hateful messages from these memorials, which undoubtedly inspires equally hateful acts. As we rethink the idea of “collective memory,” the real challenge will be enabling our institutions (legal, political and social), as well as individual designers and planners, to rewrite the narratives to reveal memories of a diverse people.